Analysis The Behavior of Oil Palm Farmers Towards People’S Business Credit at Bank Mandiri In Central Bengkulu - Ruficha Sagala; Ana Nurmalia; Herri Fariadi (UNIVED Press, Dehasen University Bengkulu, 2025)
Oil palm farmers in Central Bengkulu Regency in their farming activities require capital. The capital used is credit from Bank Mandiri. Purpose: The purpose of this study is (1) to determine the attitude of oil palm farmers toward the People's Business Credit (KUR) and (2) to determine the behavior of oil palm farmers toward the People's Business Credit (KUR) in Pagar Dewa Village, Central Bengkulu Regency. Methodology: The research method used is a descriptive quantitative method and the Fishbein model to determine the attitude of farmers toward the overall product attributes including: quality, features, and services. Results: The results show that the attitude of farmers toward the People's Business Credit at Bank Mandiri in Pagar Dewa Village, Central Bengkulu Regency, is positive. Findings: The total attitude score is 4.5, which means (Ao > 0), indicating that the farmers' attitude is positive for each attribute (quality, features, and services). Farmers' behavior (B) is influenced by two factors, namely the attitude of the farmer (Ao) and subjective norm (SN) with a value of 5.73. The result obtained for farmers' behavior toward the People's Business Credit at Bank Mandiri in Pagar Dewa Village, Central Bengkulu Regency, is 5.24 (B > 0). Novelty: The study shows that the behavior of farmers is good. Conclusion: This means that farmers may repeat their KUR borrowing at Bank Mandiri in the future. Type of Paper: Research Paper.